Line and surface defects in 5D $$N=2$$ N = 2 SCFT from matter-coupled F(4) gauged supergravity - Parinya Karndumri (European Physical Journal C: Particles and Fields)
Abstract We study supersymmetric solutions of matter-coupled F(4) gauged supergravity in the forms of $$AdS_2× S^3$$ A d S 2 × S 3 - and $$AdS_3× S^2$$ A d S 3 × S 2 -sliced domain walls with a non-vanishing two-form field from the supergravity multiplet. These two types of solutions holographically describe conformal line and surface defects within five-dimensional $$N=2$$ N = 2 SCFTs, respectively. In the case of $$SO(3)× SO(3)$$ S O ( 3 ) × S O ( 3 ) gauge group obtained by coupling F(4) supergravity to three vector multiplets, we find charged domain wall solutions describing holographic RG flows between two supersymmetric $$AdS_6$$ A d S 6 vacua with a running two-form field supporting the line and surface defects. For a particular case of one vector multiplet with $$SO(3)× U(1)$$ S O ( 3 ) × U ( 1 ) gauge group, we find solutions describing RG flows from an $$AdS_6$$ A d S 6 vacuum to physically acceptable singular geometries in the presence of defects. This class of solutions can be uplifted to type IIB theory using a consistent truncation obtained from SO(5, 5) exceptional field theory with half-maximal structures.